Frazil Ice in the Antarctic Marginal Ice Zone - Felix Paul; Tommy Mielke; Carina Schwarz; Jörg Schröder; Tokoloho Rampai; Sebastian Skatulla; Riesna R. Audh; Ehlke Hepworth; Marcello Vichi; Doru C. Lupascu (Journal of Marine Science and Engineering, 2021)
Frazil ice, consisting of loose disc-shaped ice crystals, is the first ice that forms in the annual cycle in the marginal ice zone (MIZ) of the Antarctic. A sufficient number of frazil ice crystals form the surface “grease ice” layer, playing a fundamental role in the freezing processes in the MIZ. As soon as the ocean waves are sufficiently damped by a frazil ice cover, a closed ice cover can form. In this article, we investigate the rheological properties of frazil ice, which has a crucial influence on the growth of sea ice in the MIZ. An in situ test setup for measuring temperature and rheological properties was developed. Frazil ice shows shear thinning flow behavior. The presented measurements enable real-data-founded modelling of the annual ice cycle in the MIZ.